Efektifitas Pemberian Hormon Sitokinin (BAP) dan Lama Perendaman Terhadap Pertumbuhan Sambung Pucuk Alpukat Cipedak (Persea Americana Mill) - Dicky Adi Pratama; Aditiameri Aditiameri; Darwati Susilastuti (Fakultas Pertanian Universitas Borobudur, 2023)
Avocado fruit with the Latin name Persea Americana Mill comes fromMexico and Central America. Avocado plants can grow to reach a height of 20 meters. The demand for and consumption of avocados continues to increase day by day. The more people demand avocado fruit, the more quality avocado seeds are needed. One way to get quality seeds is by vegetative propagation by grafting. Growth on shoot grafts can be accelerated by using Cytokinin growth regulators (BAP). The research was conducted in the Cipedak Avocado Plant Propagation Garden, Jagakarsa District, South Jakarta from January 2022 to March 2022. The research aims to determine the ef ectiveness of the concentration and soaking time of cytokinin growth regulators (BAP) on the growth of cipedak avocado shoots (Persea americana mill). The study was conducted using a randomized block design (RBD) consisting of 9 treatments with 3 replications, namely concentrations of 200 ppm, 400 ppm, 600 ppm, and control. From the results of the study, there was an interaction between concentration and soaking time on the percentage of live shoot grafting (%), percentage of fallen leaves (%), increase in shoot length, bud break age and rootstock diameter at 6 WAP, the ef ect of dosing and soaking time The optimum cytokinin zpt is in the S2T3 treatment.